Strategi Internet Marketing Organik Pada Penjualan Produk CV.Toserba Pesantren - Miftahol Anwar (DIGICOM : Jurnal Komunikasi dan Media, 2023)
The development of the internet brings changes in the application of the company's marketing strategy. Like CV. Toserba Pesantren, from the start of building a business, they have taken advantage of online marketing opportunities. So the point of this problem is how the internet marketing strategy uses free media in selling CV. Toserba Pesantren. This type of research uses a qualitative descriptive method with the data source is the Owner/Director of CV.Toserba Pesantren, Admin and customer CV. Toserba Pesantren with data collection namely observation, interviews and documentation so that the data analysis techniques are reduction, data presentation and conclusions. The results of this study indicate that the strategy carried out by CV. Toserba Pesantren among others, promotion or advertising through websites, search engine optimization (SEO) with an emphasis on keywords, YouTube and Whatsapp. Sales promotion through social media, discounts and special offers. Personal selling in its offline store and direct marketing via social media. The implications of this research are CV. Toserba Pesantren need to be active on several social media such as Facebook Marketplace and marketplace. In addition, it is also necessary to be active in several events, bazaars for personal selling.